PERAN KOMISI PENANGGULANGAN AIDS DAERAH (KPAD) DALAM PENANGGULANGAN HIV DAN AIDS DI KABUPATEN KOTAWARINGIN TIMUR - Akhmad Rianor Asrari Puadi; M. Bagus Qomaruddin (Universitas Airlangga, 2016)
Response to HIV and AIDS requires a approaches by the parties mutually integrated. Regional AIDS Commissions (KPAD) has a crucial role in the response to HIV and AIDS. This study aimed todescribe the role of KPAD well as some of the factors inhibiting the implementation of the HIV and AIDS in East Kotawaringin. Used qualitative methods to conduct a document review and in-depth interviews with all fi ve informants which is representative of several agencies that have links to the eff orts to combatHIV and AIDS, with purposive sampling method. The Results were analyzed by means of reduction, presentation, and verifi cation of data. Results showed reduction carried through socialization andeducation about HIV and AIDS in the various elements of society, the establishment of working group of the Pal 12, formed the group “Concerned citizens of AIDS” as well as the ARV (Antiretroviral) services is not limited to a minimum value of CD4. The results showed that KPAD role in response to HIV and AIDS can not be implemented to the fullest, this is due to several obstacles, namely the existence of localization is an determinant spread of cases, the unavailability of services and ARV in all health centers, the lack of cross-sectoral cooperation, fi nancial support from the government is minimal, and the lack of HIV and AIDS Regional Regulation (Perda).Keywords: Response to HIV and AIDS, AIDS Prevention and Control Commission (KPAD)